Immune Response in Myocardial Injury: In Situ Hybridization and Immunohistochemistry Techniques for SARS-CoV-2 Detection in COVID-19 Autopsies - Chong, Pek Yoon; Iqbal, Jabed; Yeong, Joe; Aw, Tar Choon; Chan, Kian Sing; Chui, Paul (Frontiers in Molecular Biosciences, 2021)
Coronavirus disease-19 (COVID-19) is caused by the newly discovered coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). While the lung remains the primary target site of COVID-19 injury, damage to the heart, and other organs also contribute to the morbidity and mortality of this disease. There is increasing demand to, is visualized on widely applicable techniques to visualize viral components within tissue specimens. We performed SARS-CoV-2 qRT-PCR fresh tissue from all cases; RNA-ISH and IHC for SARS-CoV-2 were performed on selected cases using FFPE tissue from heart. Here we discuss the cardiac autopsy findings of 12 ICU naïve and PCR-positive COVID-19 cases using a combination of histological, Immunohistochemical/ immunofluorescent and molecular techniques. We performed SARS-CoV-2 qRT-PCR on fresh tissue from all cases; RNA-ISH and IHC for SARS-CoV-2 were performed on selected cases using FFPE tissue from heart. Eight of these patients also had positive post-mortem serology for SARS-CoV-2. Histopathologic changes in the coronary vessels and inflammation of the myocardium as well as in the endocardium were documented which support the reports of a cardiac component to the viral infection. Immunohistochemical and immunofluorescent localisation for the viral Spike (S -protein) protein and the nucleocapsid protein (NP) were performed. As in the pulmonary reports, widespread platelet and fibrin thrombi were also identified in the cardiac tissue. The presence of these aggregates may possibly contribute to cardiac ischemia and even remodelling.